The role of DNA methylation: a challenge for the DOHaD paradigm in going beyond the historical debate. (13th October 2014) - Ngo, S.; Sheppard, A.
<x content-type="archive" xml:space="preserve">Abstract</x> A heritage of considerable research into such phenomena as parental imprinting and carcinogenesis is an almost axiomatic association of the DNA methylation epigenetic mark with the silencing of gene expression. However, the increasing technical resolution afforded by burgeoning -omics technologies reveals that a more elaborate interaction may exist between DNA methylation, within sub-regions of gene structure and/or specific dinucleotide sites, and levels of gene activity. Furthermore, seminal observations from the field of DOHaD, which clearly define the alignment of sequential epigenetic modifications and gene activity appear not to support a strictly causal relationship between DNA methylation and gene silencing. The temporal element implicit within DOHaD studies provides a useful framework within which to further explore the role of epigenetic mechanisms and in particular perhaps, to address the question of 'deterministic intent' when implicating the epigenetic regulation of gene activity in the manifestation of phenotype.